Screening and Prevention of Preeclampsia - Liona C. Poon; Daljit Sahota; Yan-Li Li; Yang Pan (Wolters Kluwer Health, 2019)
Abstract. Preeclampsia (PE) is a multisystem disorder of pregnancy classically characterized by hypertension with significant proteinuria after 20 weeks' gestation. This disorder is one of the leading causes of maternal and perinatal morbidity and mortality. PE can be subdivided into preterm PE (with delivery at <37 weeks' gestation) and term PE (with delivery at ≥37 weeks' gestation). Preterm PE is associated with a higher risk of adverse maternal and perinatal outcomes than term PE. Traditional method of screening as recommended by professional guidelines has limited predictive performance and therefore should be updated to reflect recent scientific evidence that the target of screening should be preterm PE, the best way to identify the high-risk group is the Bayes-based method that combines maternal risk factors and biomarkers, the threshold should be set at screen positive rate of 10%, aspirin should be started before 16 weeks' gestation, and the daily dose should be higher than 100 mg.